Memorandum submitted by Algeria to the Conference of Sovereigns and Heads of State of OPEC Member Countries (Algiers : Democratic and Popular Republic of Algeria, 1975)
The book sets out the main lines of Algeria's approach and ideas in the field of oil and other questions relating to development and international economic relations.
Speech delivered on March 4, 1975 at the opening of the First Conference of the Sovereigns and Heads of State of the OPEC Member Countries.
At head of title: People's Democratic Republic of Algeria.
occ 16/01/2019
Ref
Keywords: Petroleum industry and trade; Natural resources; Algeria